Potential Antioxidative Activity of Homocysteine in Erythrocytes under Oxidative Stress - Mingxin Ye; Hui Li; Hongjun Luo; Yongyin Zhou; Wenhong Luo; Zhexuan Lin (MDPI AG, 2023)
Homocysteine is an amino acid containing a free sulfhydryl group, making it probably contribute to the antioxidative capacity in the body. We recently found that plasma total homocysteine (total-Hcy) concentration increased with time when whole blood samples were kept at room temperature. The present study was to elucidate how increased plasma total-Hcy is produced and explore the potential physiological role of homocysteine. Erythrocytes and leukocytes were separated and incubated in vitro; the amount of total-Hcy released by these two kinds of cells was then determined by HPLC-MS. The effects of homocysteine and methionine on reactive oxygen species (ROS) production, osmotic fragility, and methemoglobin formation in erythrocytes under oxidative stress were studied. The reducing activities of homocysteine and methionine were tested by ferryl hemoglobin (Hb) decay assay. As a result, it was discovered that erythrocytes metabolized methionine to homocysteine, which was then oxidized within the cells and released to the plasma. Homocysteine and its precursor methionine could significantly decrease Rosup-induced ROS production in erythrocytes and inhibit Rosup-induced erythrocyte's osmotic fragility increase and methemoglobin formation. Homocysteine (but not methionine) was demonstrated to enhance ferryl Hb reduction. In conclusion, erythrocytes metabolize methionine to homocysteine, which contributes to the antioxidative capability under oxidative stress and might be a supplementary protective factor for erythrocytes against ROS damage.